2011
DOI: 10.1021/jz201175v
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Behavior of Azolium Azolate Energetic Ionic Liquids

Abstract: b S Supporting Information I onic liquids (ILs) are liquids formed by ions whose properties are tuned by the cation/anion combination. A great variety of possible cation/anion combinations drives the development of novel ILs and allows flexibility in tailoring ILs for specific applications. Azolium azolates possess superior energy density and therefore are targeted for propulsion and explosives applications. 1À4 However, the fundamental physical properties of these ILs and their full potential are not yet expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The higher fragility of ILs with aromatic groups (ranging from 117 to 130) as compared to the aliphatic groups was noted. A unique rheological behavior of azolium azolate based ILs was described by Pogodina et al This uniqueness resulted from the high elasticity of ILs at low frequency and the failure of time–temperature superposition principle. This peculiar behavior was attributed to the particular interactions in nitrogen rings of azolate ILs.…”
Section: Rheology Of Pure Ionic Liquids (Ils)mentioning
confidence: 98%
“…The higher fragility of ILs with aromatic groups (ranging from 117 to 130) as compared to the aliphatic groups was noted. A unique rheological behavior of azolium azolate based ILs was described by Pogodina et al This uniqueness resulted from the high elasticity of ILs at low frequency and the failure of time–temperature superposition principle. This peculiar behavior was attributed to the particular interactions in nitrogen rings of azolate ILs.…”
Section: Rheology Of Pure Ionic Liquids (Ils)mentioning
confidence: 98%
“…Also, such propellants can potentially have significantly higher energy density than those of hydrazine and its derivatives. Shreeve et al synthesized a number of highly energetic ionic liquids with multiple nitrogen atoms in their structures, in the hope of increasing volumetric and gravimetric energy density by introducing multiple nitrogen atoms and more nitrogen–nitrogen bonds. In lieu of this, azolium azolate ILs, salts with both cation and anion composed of heterocyclic organic ions, are now being considered as the next stage in IL propellant development, although their hypergolic property is yet to be demonstrated. A more detailed review of some of the considerations involved in developing IL propellants is given in the Supporting Information (SI).…”
Section: Introductionmentioning
confidence: 99%
“…Our own studies of ILs confirmed that ILs are complex fluids formed by heterogeneous polar and nonpolar domains, which show structure formation in their liquid phase [7], [8].The degree of structuring depends on chemical structure and type and strength of interactions (ionic, H-bonding, dipole-dipole, pi-pi). At high level of structuring we monitored even temporal network formation [8].…”
Section: Introductionmentioning
confidence: 59%
“…Our own studies of ILs confirmed that ILs are complex fluids formed by heterogeneous polar and nonpolar domains, which show structure formation in their liquid phase [7], [8].The degree of structuring depends on chemical structure and type and strength of interactions (ionic, H-bonding, dipole-dipole, pi-pi). At high level of structuring we monitored even temporal network formation [8]. These different types of interactions are the dominant factors which determine the structuring process and physical properties of ILs.Our investigations also showed [9], [10], [11] [12], [13]that ILs exhibit improved tribological properties.…”
Section: Introductionmentioning
confidence: 59%